PENGARUH KEDISIPLINAN DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMAN 1 BALUNG KABUPATEN JEMBER - jurnalmap map; Herik Mai Arifin; Hadi Susanto; Sri Juni Woro Astuti (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This study studies the description and effect of both the discipline and leadership of school principals on teacher performance at SMAN 1 Balung. Furthermore, to find out the disciplinary and leadership variables of school principals, the dominant influence on teacher performance at SMAN 1 Balung, Jember Regency. The research method used is descriptive research with quantitative analysis, with 32 teachers as respondents. The results showed the presence or absence of headmaster's leadership on the performance of the teachers of SMAN 1 Balung, Jember Regency. Simultaneously the variable of discipline and leadership of school principals on the performance of teachers of SMAN 1 Balung, Jember Regency. The dominant variable is the principal's leadership variable, because it has a t-test greater than the t-count of the disciplinary variable.Keywords: discipline, principal's leadership, teacher's performance